2017
DOI: 10.3389/fnagi.2017.00286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Demand on Functional Visual Field Performance in Senior Drivers with Glaucoma

Abstract: Purpose: To investigate the effect of cognitive demand on functional visual field performance in drivers with glaucoma.Method: This study included 20 drivers with open-angle glaucoma and 13 age- and sex-matched controls. Visual field performance was evaluated under different degrees of cognitive demand: a static visual field condition (C1), dynamic visual field condition (C2), and dynamic visual field condition with active driving (C3) using an interactive, desktop driving simulator. The number of correct resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 40 publications
5
28
1
2
Order By: Relevance
“…Several mechanisms could explain this disproportionate decrease in driving performance of patients with glaucoma during divided attention. A recent study by Gangeddula et al 9 showed that the functional field of view among patients with glaucoma results in a disproportionate reduction in performance compared with healthy individuals who have increased cognitive loading, which may help explain the results of our study. Moreover, when drivers are cognitively distracted, their eyes are fixated on a single target and eye dispersion is less.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Several mechanisms could explain this disproportionate decrease in driving performance of patients with glaucoma during divided attention. A recent study by Gangeddula et al 9 showed that the functional field of view among patients with glaucoma results in a disproportionate reduction in performance compared with healthy individuals who have increased cognitive loading, which may help explain the results of our study. Moreover, when drivers are cognitively distracted, their eyes are fixated on a single target and eye dispersion is less.…”
Section: Discussionsupporting
confidence: 67%
“… 7 Although glaucoma has been previously associated with increased risk for motor vehicle crashes, 5 , 8 the conditions associated with increased risk in this population have not been well clarified. Gangeddula and colleagues 9 have shown that the functional field of view of patients with glaucoma experiences a disproportionate reduction compared with that of healthy individuals under increased cognitive loading. Moreover, when drivers are cognitively distracted, their eyes are fixated on a single target and eye dispersion is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The EyeWorks™ Analyze software (EyeTracking Inc., 2011) was used to transform pupil dilation data from the right eye to the scaled ICA that ranges between 0 and 1. Although right eye and left eye ICA results were strongly correlated ( r = 0.70, p < 0.001), right eye ICA data was shown interpretable results compared to the left eye ICA data which was also consistent with the previous literature (Gangeddula et al, 2017 ; Ranchet et al, 2017b ). Recorded videos were analyzed to find start- and end-time points of each LN load.…”
Section: Methodssupporting
confidence: 91%
“…Poorer performance on cognitive tests, such as the Montreal Cognitive Assessment, have also been linked to greater visual field loss 13,14 and thinner retinal nerve fibre layer thickness in individuals with or without glaucoma 15 . Other studies 16–19 have similarly demonstrated that individuals with glaucoma tend to perform more poorly on various cognitive tests such as the MMSE and a 6‐item cognitive impairment test. Conversely, other population‐based studies 20,21 failed to find a relationship between glaucoma and impaired cognitive function, particularly after controlling for age and other potential confounders such as co‐morbidities.…”
Section: Introductionmentioning
confidence: 99%